Pengaruh Live Streaming Penjualan, Content Marketing, dan Customer Reviews Terhadap Keputusan Pembelian Pada UMKM Makanan Ringan Cemilanki di Kabupaten Wonosobo - Irfan Romadhon; Murry Harmawan Saputra; Dedi Runanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The numerous conveniences offered by e-commerce platforms provide added value for consumers, as they can easily compare prices, product features, and brand reputation within seconds. This condition makes purchase decisions no longer based solely on needs, but also on experience, emotional value, and perceptions formed through digital interactions. An individual’s purchase decision can be influenced by various factors, including sales live streaming, content marketing, and customer reviews. The purpose of this study is to examine the effect of live streaming, content marketing, and customer reviews on purchase decisions at the Cemilanki snack MSME in Wonosobo Regency. The population in this study consists of individuals who have made purchases from the Cemilanki snack MSME through e-commerce platforms such as Shopee, TikTok Shop, or Tokopedia. The sampling technique used was purposive sampling. The total sample consisted of 150 respondents. Data were collected using a questionnaire that had been tested for validity and reliability. Data analysis was conducted using multiple linear regression analysis. The results of the study indicate that sales live streaming has a positive and significant effect on purchase decisions, content marketing has a positive and significant effect on purchase decisions, and customer reviews have a positive and significant effect on purchase decisions at the Cemilanki snack MSME in Wonosobo Regency.